2022
DOI: 10.1001/jamainternmed.2022.5074
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Computer-Tailored Print Feedback, Motivational Interviewing, and Motivational Enhancement Therapy on Engagement in Advance Care Planning

Abstract: ImportanceThere is a tension between clinician-led approaches to engagement in advance care planning (ACP), which are effective but resource-intensive, and self-administered tools, which are more easily disseminated but rely on ability and willingness to complete.ObjectiveTo examine the efficacy of computer-tailored print feedback (CTPF), motivational interviewing (MI), and motivational enhancement therapy (MET) on completion of a set of ACP activities, each as compared with usual care.Design, Setting, and Par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…One of the nurses had previous training in motivational interviewing 28 and behavioral activation and suggested those techniques be incorporated into future trainings. Specifically, the nurse applied motivational interviewing skills when initiating goals-of-care conversations 29 . Both nurses expressed using the Conversation Starter Kit 23 was useful to guide goals-of-care discussions.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…One of the nurses had previous training in motivational interviewing 28 and behavioral activation and suggested those techniques be incorporated into future trainings. Specifically, the nurse applied motivational interviewing skills when initiating goals-of-care conversations 29 . Both nurses expressed using the Conversation Starter Kit 23 was useful to guide goals-of-care discussions.…”
Section: Resultsmentioning
confidence: 99%
“…They found patients receiving the support program gave significantly more cues that they wished to discuss prognosis, end-of-life care, and future care options; however, they failed to ask specific questions. This finding implies that applying motivational interviewing techniques may motivate patients to ask direct questions about prognosis and end-of-life care from trusted clinicians 28,29 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study showed high levels of ACP completion and this appeared quite high for subjects who eventually died. Our nurses had training in motivational interviewing, which was shown to increase ACP readiness in a Veterans Affairs study compared to usual care [ 18 , 34 , 35 ]. Nurses were also trained in Respecting Choices, an established ACP engagement program [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Since then, the approach has been further developed as a conversation style for strengthening a person’s own motivation, commitment, and self-efficacy to change [ 1 ]. An important concept in MI is that of a particular MI spirit, which includes encouraging collaboration, conveying acceptance, showing empathy, and evoking the patient’s own reasons for change [ 1 ].MI is mainly used in healthcare and social service settings, in brief interventions addressing, e.g., alcohol or drug use, gambling or smoking cessation, but also in supporting individuals to engage in treatment that promotes health [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%